Zoonotic Parasites and Their Association With Human Activities in Northern Tanzania: An Integrated Ecosystem Approach for One Health - Barakaeli Abdieli Ndossi; Eblate Ernest Mjingo; Hansol Park; Dongmin Lee; Mohammed Mebarek Bia; Heejae Yang; Sungbo Seo; Keeseon S. Eom (Journal of Parasitology Research)
The community’s awareness of the prevalence and impact of zoonotic diseases has been significantly underestimated, leading to insufficient implementation of control measures. This study was carried out in Northern Tanzania between 2019 and 2023 to investigate zoonotic parasites and the risks associated with human activities that contribute to zoonotic diseases. Cross-sectional surveys were conducted in 12 villages, including nine in Loliondo Division and three in Babati District. Focus Group Discussions and Key Informant Interviews were conducted to assess the community’s knowledge and practices regarding the risks associated with zoonotic diseases in the surveyed areas. A total of 255 samples were collected from various sources, including latrines, households, livestock enclosures, domestic dogs, and chickens. Out of these samples, 152 tested positive for identifiable parasite eggs and oocysts. These parasites included hookworms (21.7%), Trichuris sp. (14.5%), Strongyloides sp. (13.8%), Eimeria sp. (19.7%), Taeniids (5.9%), Hymenolepis sp. (3.3%), Spirometra sp. (2.6%), and Dipylidium sp. (0.7%). Taeniids and Spirometra species were predominantly found in villages near protected areas such as Arash Sokoni, Oloipiri, Sukenya, Wasso, Orkuyiene, Haytemba, and Loliondo. Hookworms were most commonly detected in Arash Sokoni, Loliondo, Isuguro, and Hyatemba, while Strongyloides sp. was prevalent in Wasso, Sukenya, and Olobo villages. The quantitative analysis reveals significant associations between hygiene practices, proximity to livestock enclosures, ecological factors, and human–animal interaction, highlighting their pivotal roles in determining soil-transmitted helminth (STH) prevalence across different villages. This study reveals that there was a generally low level of awareness regarding zoonotic diseases and STHs. The detection of STH samples, combined with the limited understanding of zoonotic diseases, emphasizes the importance of taking proactive measures to reduce transmission risks. Prioritizing education and promoting awareness along with implementing comprehensive strategies are essential steps to effectively tackle the problems linked to STH infections and substantially lessen the public health burden caused by zoonotic diseases.